Ways to Increase the Participation of Students In Information Technology Classes - Ismanova Klara Dulanboyevna; Isomaddinov Usmonali Mamurjonovich (Peerian Journals Publishing, 2023)
In this article, сonclusions and suggestions formed as a result of deploying innovasion technologies which are considered to be essential to use in every processes of education will be stated. Some factors stimulating the educational activity of students are analyzed, and examples are given. Questions and situations used in problem-based learning are applicable to the learning process of information technology
Keywords: cognitive activity; systematic approach; pedagogical technology